Analisis Kebutuhan E-Modul Biologi Terintegrasi Nilai IMTAQ DiKelas XI SMA Negeri 1 Pekanbaru - Salsa Mulani Putri; Siti Robiah; Nurkhairo Hidayati (CV. SINAR HOWUHOWU, 2026)
This study aimed to identify the need for Biology e-modules integrated with faith and piety (IMTAQ) values by teachers and eleventh-grade students at SMA Negeri 1 Pekanbaru. The e-module is an electronic-based teaching material accessible through computers or Android devices and contains text, images, videos, and learning content integrating IMTAQ values. This study was conducted in the 2025/2026 academic year using a descriptive qualitative and quantitative approach (mixed methods). Data were collected through interviews with Biology teachers and questionnaires distributed to 30 eleventh-grade students. The results showed that teachers had not yet used independently developed e-modules, and the integration of IMTAQ values in Biology learning was still limited and not systematic. Based on the data analysis, it can be concluded that both teachers and students highly need an IMTAQ-integrated Biology e-module to enhance students’ understanding of the material, learning motivation, and the development of religious character.